2021
DOI: 10.2147/ndt.s290793
|View full text |Cite
|
Sign up to set email alerts
|

Hummingbird Study: Results from an Exploratory Trial Assessing the Performance and Acceptance of a Digital Medicine System in Adults with Schizophrenia, Schizoaffective Disorder, or First-Episode Psychosis

Abstract: Purpose Symptoms of psychotic disorders can complicate efforts to accurately evaluate patients’ medication ingestion. The digital medicine system (DMS), composed of antipsychotic medication co-encapsulated with an ingestible sensor, wearable sensor patches, and a smartphone application, was developed to objectively measure medication ingestion. We assessed performance and acceptance of the DMS in subjects with psychotic disorders. Methods This was an 8-week open-label, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 20 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…35,44 For example, a 2021 study of a digital antipsychotic medication reported 63.4% of study days with good sensor patch coverage, detected 56.4% of ingestible event-markers, generated an adherence metric of 86.6%, and was considered satisfactory and helpful by a majority of patients with SMI. 45 A recent, phase 3b, mirror-image, open-label, single-arm clinical trial compared outcomes for patients with schizophrenia who had a history of psychiatric hospitalization when they used standard-of-care (SOC) oral antipsychotics versus when they used ABILIFY MYCITE ® (aripiprazole tablets with sensor [AS]). 46 AS consists of aripiprazole tablets embedded with an ingestible event-marker sensor, wearable sensor patches and a smartphone application, and is indicated for the treatment of adults with schizophrenia or bipolar I disorder, and as adjunct treatment for adults with major depressive disorder.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…35,44 For example, a 2021 study of a digital antipsychotic medication reported 63.4% of study days with good sensor patch coverage, detected 56.4% of ingestible event-markers, generated an adherence metric of 86.6%, and was considered satisfactory and helpful by a majority of patients with SMI. 45 A recent, phase 3b, mirror-image, open-label, single-arm clinical trial compared outcomes for patients with schizophrenia who had a history of psychiatric hospitalization when they used standard-of-care (SOC) oral antipsychotics versus when they used ABILIFY MYCITE ® (aripiprazole tablets with sensor [AS]). 46 AS consists of aripiprazole tablets embedded with an ingestible event-marker sensor, wearable sensor patches and a smartphone application, and is indicated for the treatment of adults with schizophrenia or bipolar I disorder, and as adjunct treatment for adults with major depressive disorder.…”
Section: Dovepressmentioning
confidence: 99%
“… 35 , 44 For example, a 2021 study of a digital antipsychotic medication reported 63.4% of study days with good sensor patch coverage, detected 56.4% of ingestible event-markers, generated an adherence metric of 86.6%, and was considered satisfactory and helpful by a majority of patients with SMI. 45 …”
Section: Introductionmentioning
confidence: 99%
“…Abilify iDAS is intended to augment treatment as usual by a physician, a model incorporated into the MindLAMP [34] and Horyzons platforms [35]. Abilify iDAS and these platforms have consistently demonstrated feasibility of use and efficacy with treatment as usual in psychiatric patients with SMI [34,[36][37][38][39][40][41]. These reports substantiate the proposal that Abilify iDAS could support the TR.…”
Section: Introductionmentioning
confidence: 52%
“…Patients were asked to use the DMS for 90 days, at which time they, along with their provider, could decide whether to continue using the DMS beyond 90 days and up to the full 12 months of study participation. Compared with previous studies using a DMS with an ingestible sensor pill for a period of 8 [13] or 12 [14] weeks, the use of the DMS lasted up to 12 months, which provided insight into DMS use that was 90 days or longer (12/21, 57%), with 29% (6/21) of respondents opting to use the DMS for 180 days or more.…”
Section: Principal Findingsmentioning
confidence: 94%
“…In another trial using the same DMS [13] as in our study, adherence was measured by the proportion of days with good DMS patch coverage (ingestible event marker registration). However, in our study, medication adherence was assessed by the PDC on aripiprazole using pharmacy record data.…”
Section: Principal Findingsmentioning
confidence: 99%